Syntheses and characteristics of water-soluble, pyridine-based poly(aryleneethynylene)s - Seehafer, Kai; Bender, Markus; Schwaebel, S. Thimon; Bunz, Uwe H. F. (Macromolecules, 2014)
We have prepared a series of water-soluble, pyridine-containing poly(aryleneethynylene)s (PAEs), consisting of alternating units of substituted ethynylpyridines and ethynylbenzenes. Water solubility is achieved by branched oligoethylene glycol (swallowtail) side chains. The fluorescence quantum yield (ϕ) of these PAEs was studied in dependence of their structure. The emissive quantum yield is not very dependent upon the number and position of the swallowtail substituents as long as their number suffices to dissolve the PAE in water. Attachment of a carboxylate group onto the pyridine unit decreases ϕ of the PAEs. All of the PAEs were metallo-reactive. Hg2+ and Fe3+ ions quench the fluorescence of the PAEs, while other metal cations (Cd2+, Zn2+, Cu+, Cu2+) only quench the fluorescence of some of the PAEs. According to the Stern-Volmer quenching constants, some of the PAEs are more sensitive toward quenching than the well-documented dicarboxylate-PPEs.